Interleaved reception method for restored vector quantization image - Iman Elawady; Abdelmounaim Moulay Lakhdar; Mustapha Khelifi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The transmission of image compression by vector quantization produce wrong blocks in received image which are completely different to the original one that makes the restoration process too hard because we don’t have any information about the original blocks. As a solution of this problem we try to keep the maximum of pixels that form the original block by building new blocks. Our proposition is based on decomposition and interleaving. For the simulation we use a binary symmetric channel with different BER and in the restoration process we use simple median filter just to check the efficiency of proposed approach.